Major factors influencing student engagement in Ethiopian higher education institutions: Evidence from one institution - Mekonnen Haile Faro; Tariku Sime Gutu; Adula Bekele Hunde (PLoS ONE, 2025)
This study investigates factors influencing student engagement in Ethiopian higher education, focusing on self-efficacy, teacher support, and technology support at Mattu University. A cross-sectional survey design was employed; involving 620 undergraduate students selected using stratified sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) to assess the impact of these variables on student engagement. The findings reveal that teacher support, technology support, and self-efficacy collectively explain 69% of the variance in student engagement, with teacher support identified as the strongest predictor. The results highlight the importance of supportive teacher-student relationships, accessible digital resources, and students’ confidence in their academic abilities for fostering engagement. The study underscores the need for improved teacher preparation, diverse instructional strategies, and enhanced access to digital resources. These findings offer practical recommendations for policymakers and educational institutions in Ethiopia to create more engaging learning environments, ultimately enhancing academic success and retention in higher education.